Elastic and plastic deformation of carbon nanotubes - Shima, Hiroyuki (CRC Press, 2013)
Carbon nanotubes offer huge potential in so many fields due in part to their significant mechanical properties, including extraordinary rigidity, resilience, toughness, and flexibility. Mechanical deformation of carbon nanotubes is known to cause considerable changes in their physical and chemical properties through the nontrivial structure-property correlation. A strong understanding of their deformation mechanism and available geometry is, therefore, crucial to developing nanotube-based applications. This book concentrates on the remarkable mechanical properties of carbon nanotubes, covering.